2019
DOI: 10.1002/mrd.23130
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of Annexin 3 in diapause embryo restart of Artemia sinica and in response to stress of low temperature

Abstract: Annexins are highly conserved and ubiquitous in various somatic cell types. They are involved in membrane transport and a range of calcium-regulated activities on the cell membrane surface, including vesicular transport, membrane fusion in exocytosis, signal transduction, and formation of calcium channels. They also regulate inflammatory response, cell differentiation, and interaction between cytoskeletal proteins. In this study, for the first time, an ANX3 gene from Artemia sinica (As-anx3) was cloned. The As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…At the molecular level, diapause often involves the activation or repression of specific genes responsible for stress resistance, metabolic arrest and long‐term survival (Fielenbach & Antebi, 2008; Li et al., 2019; Park et al., 2020). In this study, by comparing cells between NPP and PP, we observed that podocyst formation did not substantially alter cell type identity but did lead to changes in the composition of cell types and the relative proportions of cell‐type‐specific gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, diapause often involves the activation or repression of specific genes responsible for stress resistance, metabolic arrest and long‐term survival (Fielenbach & Antebi, 2008; Li et al., 2019; Park et al., 2020). In this study, by comparing cells between NPP and PP, we observed that podocyst formation did not substantially alter cell type identity but did lead to changes in the composition of cell types and the relative proportions of cell‐type‐specific gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution strategy for A. sinica living through the disadvantageous conditions benefits from the ability of females that produce diapause cysts before the onset of adverse environmental challenges, such as fluctuation of salinity and temperature due to oncoming winter [27,28,29]. To explore the role which RAD9 may be involved in during natural occurrence of diapause, in the present study, the high salinity and low-temperature conditions were repeated to study the expression of As –RAD9 in these stress processes.…”
Section: Discussionmentioning
confidence: 99%
“…The collection and preparation of A. sinica samples were carried out according to our previous studies [28,37].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations